A practical and highly efficient synthesis of lennoxamine and related isoindolobenzazepines - Poolsak Sahakitpichan (2018)
Lennoxamine and related isoindolobenzazepines were prepared in high yield by intramolecular condensation of aldehyde isoindolones under basic conditions followed by catalytic hydrogenation of the resulting dehydroisoindolobenzazepines. © 2004 Elsevier Ltd. All rights reserved.